Fabaceae endémicas del Perú - Baldeón, Severo (2006)
The Fabaceae are represented in Peru by 145 genera and 1000 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly trees and shrubs. Here we recognize as Peruvian endemics 234 species and 40 varieties in 47 genera. One genus, Weberbauerella, is endemic to Peru. Undoubtedly, Lupinus is the genus with the largest number of endemic species in the family, and at the same time, the genus that most needs detailed taxonomic studies and more collection. Endemic Fabaceae are found in almost all regions, mainly Mesoandean, Humid and Dry Puna, and Very Humid Montane Forests, between 1100 and 4800 m elevation. We applied IUCN categories and criteria to 203 taxa. Seventeen endemic taxa have been recorded within Peru’s protected areas system.